The Effect of shear connection on half precast concrete slabs - Nur Idanie Rapian (School of Environmental Engineering, University Malaysia Perlis, 2012)
This study introduces a semi- fabricated system for the construction of floor slabs. A prefabricated half precast slab is a manufacturing process, where consist two layer of concrete. Bottom layer fabricate in the factory initially as a formwork, and top layer cast in-situ during construction. The use of prefabricated half precast slabs is an alternative solution to overcome many problems in construction sector such as formwork problem, concrete waste, construction delay, finishing and others. Prefabricate half precast slab also one of the part Industrialized Building Systems (IBS). The use of fabricated building component gives economic implication to the contractor in term of labour shortage, reducing time consuming and others. In this study, the uses of Lightweight Aggregates Concrete (LWAC) as bottom layer by using Palm Oil Clinker (POC) give two more advantages. The product of half precast slab will lighter than normal concrete and also will reduce residue of the boiler waste at palm oil mill. To investigate the bond strength and compressive strength in composite slabs, seven slab specimens having different materials, cases and presence of shear connectors between the two layers were cast and tested under flexural test accordance to BS 5950: Part 4: 1994. Test results shown that the presences of bar reinforcement as interlocking mechanism produce higher horizontal shear bond strength and compressive strength in composite slabs. Meanwhile, the structural behaviour and the horizontal shear bond strength of the LWAC slabs are nearly similar to the conventional concrete slabs, which in turn will reduce the cost of the composite slab. Capacity of half solid slab using LWAC can sustains 20 kN as temporary structure.